Testosterone Deficiency in Sickle Cell Disease: Recognition and Remediation - Musicki, Biljana; Burnett, Arthur L. (Frontiers in Endocrinology, 2022)
Hypogonadism is common in men with sickle cell disease (SCD). Primary hypogonadism is established as the principal cause for this hormonal abnormality. The underlying mechanism for primary hypogonadism was elucidated in a mouse model of SCD, and involves increased NADPH oxidase-derived oxidative stress in the testis, which reduces protein expression of a steroidogenic acute regulatory protein and cholesterol transport to the mitochondria in Leydig cells. Hypogonadism affects physical growth and development, cognition and mental health, sexual function, and fertility. However, it is not understood whether declines in physical, psychological, and social domains of health in SCD patients are related to low testosterone, or are consequences of other abnormalities of SCD. Priapism is one of only a few complications of SCD that has been studied in the context of hypogonadism. In this condition of prolonged penile erection in the absence of sexual excitement or stimulation, hypogonadism exacerbates already impaired endothelial nitric oxide synthase/cGMP/phosphodiesterase-5 molecular signaling in the penis. While exogenous testosterone alleviates priapism, it disadvantageously decreases intratesticular testosterone production. In contrast to treatment with exogenous testosterone, a novel approach is to target the mechanisms of testosterone deficiency in the SCD testis to drive endogenous testosterone production, which potentially decreases further oxidative stress and damage in the testis, and preserves sperm quality. Stimulation of translocator protein within the transduceosome of the testis of SCD mice reverses both hypogonadism and priapism, without affecting intratesticular testosterone production. Ongoing research is needed to define therapies that restore endogenous testosterone production in a physiologic, mechanism-specific fashion.